THE INFLUENCE OF URBAN PLANNING CONTEXT ON THE INTERIOR DESIGN OF MODULAR HOUSING - Колобанова, Д. А.; Третяк, Ю. В. (Art and Design, 2024)
Purpose of the work is to determine the influence of the urban planning context on the interior design of modern residential modular buildings, as well as to identify the connection between the internal environment of modular housing and the surrounding environment. Methodology. The study is based on a combination of theoretical generalization of the collected data with a systemic approach. The source base of this work is examples of world experience in the design of modular housing, the layout of their premises, and the placement of furniture and equipment in the structure of the interiors of various types of residential units. Results. Following the set goal and objectives, the work investigates the issue of the influence of the urban planning context on the formation of the interior environment of residential modular buildings of various types, which are determined depending on the location of the building in the environment. The main results of the study are as follows: the most common urban planning situations for the placement of modular residential buildings have been identified; the characteristic typological features of the design of residential modules and their interiors, located in various urban planning situations, have been identified; It is proposed to consider the urban planning context, architecture and the subject-spatial environment of residential modules as a single spatial system; promising directions for the development and improvement of the methodology for the design of interiors and equipment of modular housing are identified. Scientific novelty of the study lies in identifying the relationship between the urban planning context and the subject-spatial environment of residential modules. The interior is considered as an element of an interconnected system that combines different levels of the environment - urban planning, architecture, interior, and subject. Such an approach can be considered promising in terms of the formation of new strategies, methods, and tools for the complex design of residential modules. Practical significance. The results of the study can be used by architects and designers in the process of designing and improving the internal space of residential modular buildings, taking into account the specifics of a particular urban planning context.